2009
DOI: 10.1002/syn.20711
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal binge‐like alcohol exposure decreases dendritic complexity while increasing the density of mature spines in mPFC Layer II/III pyramidal neurons

Abstract: Prenatal exposure to alcohol in humans can result in a wide range of deficits collectively referred to as Fetal Alcohol Spectrum Disorders. Of these deficits, cognitive impairments are among the most debilitating and long-lasting. Specifically, cognitive impairments in executive functioning suggest damage to the prefrontal cortex (PFC). Several external stimuli, such as morphine, chronic stress and maternal stress have been found to alter the dendritic structure of cells within the PFC. In this study, three gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
71
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 56 publications
(74 reference statements)
6
71
0
Order By: Relevance
“…Such damage may contribute to the impaired impulse control and social deficits observed in children with FASD throughout life. In particular, rodent models of developmental alcohol exposure result in increased caspase-3 expression in the central nucleus of the amygdala (Mitchell & Snyder-Keller, 2003), long-term reductions to amygdalar opioid signaling (Lugo, Wilson, & Kelly, 2006), and altered synaptic connectivity and neuronal loss in the amygdala (Balaszczuk, Bender, Pereno, & Beltramino, 2011; Cullen et al, 2013; Zhou et al, 2010) and the prefrontal cortex (Hamilton, Whitcher, & Klintsova, 2010; Ikonomidou et al, 2000; Lawrence, Otero, & Kelly, 2012; Whitcher & Klintsova, 2008). Dysfunction of these brain areas could contribute to disruptions in social and play behavior observed in AE rats.…”
Section: Discussionmentioning
confidence: 99%
“…Such damage may contribute to the impaired impulse control and social deficits observed in children with FASD throughout life. In particular, rodent models of developmental alcohol exposure result in increased caspase-3 expression in the central nucleus of the amygdala (Mitchell & Snyder-Keller, 2003), long-term reductions to amygdalar opioid signaling (Lugo, Wilson, & Kelly, 2006), and altered synaptic connectivity and neuronal loss in the amygdala (Balaszczuk, Bender, Pereno, & Beltramino, 2011; Cullen et al, 2013; Zhou et al, 2010) and the prefrontal cortex (Hamilton, Whitcher, & Klintsova, 2010; Ikonomidou et al, 2000; Lawrence, Otero, & Kelly, 2012; Whitcher & Klintsova, 2008). Dysfunction of these brain areas could contribute to disruptions in social and play behavior observed in AE rats.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol's teratogenic effects on forebrain development, the medial prefrontal cortex and hippocampus in particular, can be seen via reduced cell numbers (Livy et al, 2003;Mihalick et al, 2001) and constrained or altered spine density and dendritic complexity (Hamilton et al, 2010;Tanaka et al, 1991). Postnatal exposure is reported to diminish or alter hippocampal neurogenesis, stmctural plasticity, yV-methyl-D-aspartate receptor (NMDAR)-dependent long-term potentiation (LTP), and CAl learning-dependent excitatory unit activity (Bonthius & West, 1991;Klintsova et al, 2007;Lindquist ct al, 2013;Livy et al, 2003;Puglia & Valenzuela, 2010).…”
mentioning
confidence: 97%
“…Neuroimaging studies have revealed structural and functional abnormalities in the hippocampus and prefrontal cortex of children with FASD (Davis et al, 2011), contributing to the impaired performance seen in both children and adults with FASD when tested in a variety of forebrain-dependent cognitive (e.g., learning and memory) tasks (Mattson et al, 2011). Ethanol (EtOH) exposure over postnatal days (PD) 4 to 9 in rodents, a period comparable to the human third trimester (Bayer et al, 1993), also impairs forebrain neurodevelopment, producing significant reductions in dendritic spine density, neurogenesis, and long-term potentiation (LTP) (Hamilton et al, 2010;Klintsova et al, 2007;Puglia and Valenzuela, 2010).…”
mentioning
confidence: 98%